2014
DOI: 10.1136/bcr-2013-202650
|View full text |Cite
|
Sign up to set email alerts
|

Twin athlete brothers with open physes operated for ACL reconstruction on the same day, but with different elapsed times after injury: a 5-year follow-up

Abstract: We present the case of twin brothers with open physes who practiced judo to a high level and were operated on the same day for anterior cruciate ligament reconstruction. One of them was injured a year before surgery, and the other was injured a month before the procedure. The brother who chose to undergo a conservative treatment sustained meniscus injury afterwards and showed lower objective results when evaluated 5 years after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Sonn and Caltoum reported a case of 15-year-old monozygotic brothers that were high-level athletes with congenital absence of the right ACL that subsequently both underwent ACL construction with bone-patellar tendon-bone autograft [18]. Astur et al reported a case of twin brothers who were both professional judo athletes that sustained similar ACL tears one year apart but underwent surgery on the same day by the same surgeon that utilized the same technique and graft type (hamstring tendon graft with femoral and tibial interference screws) [6]. Both patients were Tanner stage III at the time of their ACL tears.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonn and Caltoum reported a case of 15-year-old monozygotic brothers that were high-level athletes with congenital absence of the right ACL that subsequently both underwent ACL construction with bone-patellar tendon-bone autograft [18]. Astur et al reported a case of twin brothers who were both professional judo athletes that sustained similar ACL tears one year apart but underwent surgery on the same day by the same surgeon that utilized the same technique and graft type (hamstring tendon graft with femoral and tibial interference screws) [6]. Both patients were Tanner stage III at the time of their ACL tears.…”
Section: Discussionmentioning
confidence: 99%
“…Limited research is available studying twins with ACL tears and the risk factors associated with them [6][7]. Enhanced knowledge of genetic contribution to ACL injuries is important to better understand predisposing factors and to develop preventative approaches [8].…”
Section: Introductionmentioning
confidence: 99%
“…The ACL does not heal following lesions, and surgical reconstruction is the treatment of choice in most cases [ 4 , 5 ]. Reconstructive surgery aims to restore the kinematics and stability of the injured knee, which allows a return to sports and may help to prevent osteoarthritis in the long term [ 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Tanner sexual staging system is currently used to define patients’ treatment strategy 2 4. Currently, young patients with immature or nearly mature skeletons (Tanner III and IV) are believed to be ready to undergo arthroscopic transphyseal ligament reconstruction 13.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, young patients with immature or nearly mature skeletons (Tanner III and IV) are believed to be ready to undergo arthroscopic transphyseal ligament reconstruction 13. There is no consensus for patients at Tanner stages I and II 2 14. A transepiphyseal ACL reconstruction procedure is recommended for Tanner stage II.…”
Section: Introductionmentioning
confidence: 99%